The Ability of Plants to Accumulate Aurum (Au) in the Central Kapuas Gold Mining Region - Sunariyati, Siti (Proceeding International Conference on Global Resource Conservation, 2013)
The purpose of this study is to (1) inventory and identify a number of plant species that can be used as indicators of the presence of gold. (2) Analyze the content of Au in plant specimens which are suspected as a pointer in the gold mining region. (3) Study the transport mechanism of Au in plants. The research activity consists of two stages. Stage I is identifying the plants species in the gold mining region which is believed to locals as an indicator of the presence of gold. Stage II is gathering scientific evidence through laboratory analysis, and verified by the knowledge society. The inventory and identification results in the finding of 11 species of plants that are believed by the gold miners as indicators of the presence of gold, which are Tristania merguensis (Griff)., Melaleuca soulatrii Lin., Syzygium zeylanicum (L) DC., Dillenia excelsa Gilg., Shorea maxwelliana King., Calophyllum hosei Ridl., Dipterocarpus octovus King., Agrostistachys sessilifolia (Kurz) Pax & Hoffm., Gluta renghas L., Combretocarpus suolatrii Roxb., and Memecylon myrsinoides. Blume. Based on the results of a calculation with a quantitative approach, the value of the interests of the species (Fidelity level) shows that Katune (A. sessilifolia (Kurz) Pax & Hoffm) has the highest FL value of interest (48.48%). Similarly, the value (Use Value) for Katune (A. sessilifolia (Kurz) Pax & Hoffm) is higher than the others. The laboratory analysis of the 11 species of plants show that they can accumulate the Au in roots stems and leaves tissue in varying levels. The highest average value is found in the stems of 130.36 ppb, in leaves 85.45 ppb, and the lowest is on the roots of 64.72 ppb. The correlation analysis also shows that the accumulation of Au in plants has correlation with the presence of Au in the soil. This indicates that the plants are able to take and to transport Au from the soil through the roots then being accumulated in the stem and leaves.Â Keywords: Ability of plants, accumulation of Au, gold mining